"Chinese, Yet Not Chinese": creolized Babas, China-born Chinese, and their changing relationships in Singapore after 1870s - Ong, Soon Keong (2023)
This article examines the factors behind the changing relationships between Chinese born in Singapore, i.e.the so-called Babas, and Chinese born in China from the late nineteenth century to the early 1930s. It observes that while their interactions were congenial and interdependent in the nineteenth century, they became increasingly contentious and antagonistic into the early twentieth century. Because the Babas had settled outside China and created a creolized culture through localization and Westernization, their supposed straying from Chinese culture and distancing from China were used by scholars and the Chinese themselves to explain the growing gulf between the Babas and the China-born. But as this article argues, in the period under study, the tension and animosity between the two Chinese communities ran deeper than mere cultural differences, as they were aggravated by social changes, economic competitions, and divergent political allegiances.